A Model of Satisfaction Promotion for International Students in Universities of Medical Sciences in Tehran - Kobra Nakhoda; Mohammad Ali Hosseini; Kamran Mohammadkhani; Nader Gholi Ghorchian (Tehran University of Medical Sciences, 2020)
Background and Aim: International student satisfaction is a vital element in international universities and one of the promotion methods in the global ranking, and is considered as a competitive factor. Materials and Methods: The research method is mixed (quantitative-qualitative) of exploratory-confirmatory type. The statistical population includes experts, international department managers and foreign students(1352 people) in three universities of medical sciences in Tehran, Shahid Beheshti and Iran. The sampling method is qualitative, purposeful and the sample size is 21 professors. In a small part of the multi-stage cluster method, 450 international students were selected. The research tool was a semi-structured interview in the qualitative part of the interview and a researcher-made questionnaire in the quantitative part. Results: According to the research results, the most influential factor in the foreign studentschr('39') satisfaction model includes virtual services(0.84), loyalty(0.81), university reputation and rank (0.78), admission process(0.75), Research services(0.72), Staff and management services(0.71), International services(0.70), Educational services(0.68), Health services(0.67), Welfare services(0.65), Financial facilities(0.64), university infrastructure(0.63) and cultural services(0.61). Conclusion: In order to attract financial resources, international competition, improve regional and global ranking, universities should consider and plan the priorities of the proposed satisfaction model to improve the level of satisfaction of foreign students.